Approximate controllability of semilinear control systems in Hilbert spaces - Şemi, Nidai; Mahmudov, Nazim I. (Turkic World Mathematical Society, 2012)
This paper deals with the approximate controllability of semilinear evolution systems in Hilbert spaces. Sufficient condition for approximate controllability have been obtained under natural conditions.
Keywords: Control theory, Approximation theory; Mathematical research, Hilbert space, Research; Control systems, Approximations